Composite electrode, preparation method, photoelectric device and display device

By using composite electrodes containing permanent magnet materials in optoelectronic devices, the problem of resistance changes in optoelectronic devices in magnetic field environments is solved, and performance stability and service life are improved.

CN119233671APending Publication Date: 2024-12-31TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310798196.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The resistance of existing optoelectronic devices will change in magnetic field environments, resulting in unstable performance.

Method used

A composite electrode is used, including a first electrode layer, a magnetic functional layer and a second electrode layer, wherein the magnetic functional layer contains a permanent magnet material, such as a rare earth permanent magnet alloy, to maintain the resistance stability by magnetization under a magnetic field environment.

Benefits of technology

It improves the performance stability of optoelectronic devices in magnetic field environments, ensures the stability of resistance values, thereby extending the service life of the device and improving current efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119233671A_ABST
    Figure CN119233671A_ABST
Patent Text Reader

Abstract

The invention provides a composite electrode, a preparation method, a photoelectric device and a display device, and belongs to the technical field of display. The composite electrode comprises the permanent magnet material, so that the magnetized composite electrode can maintain a relatively stable resistance value in a magnetic field environment, and the performance stability of the photoelectric device with the composite electrode in the magnetic field environment is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of optoelectronic devices, and in particular to a composite electrode, a preparation method, an optoelectronic device and a display device. Background Art

[0002] Electrodes are important components of optoelectronic devices, and the stability of electrodes has a great impact on the performance of optoelectronic devices. However, the resistance of existing electrodes (cathode or anode) will change in a magnetic field environment, resulting in unstable performance of optoelectronic devices with such electrodes. Summary of the invention

[0003] The present invention provides a composite electrode, a preparation method, a photoelectric device and a display device to solve the problem that the current photoelectric device has unstable performance in a magnetic field environment.

[0004] In one aspect, the present application provides a composite electrode, comprising: a first electrode material and a first permanent magnetic material.

[0005] In some embodiments of the present application, the composite electrode includes a first electrode layer, a first magnetic functional layer, and a second electrode layer stacked in sequence;

[0006] The first electrode layer includes the first electrode material, and the first magnetic functional layer includes the first permanent magnetic material.

[0007] In some embodiments of the present application, the material forming the second electrode layer is the same as the material forming the first electrode layer;

[0008] And / or, the first magnetic functional layer further includes the first electrode material;

[0009] And / or, the thickness of the first electrode layer is 3nm-10nm;

[0010] And / or, the thickness of the first magnetic functional layer is 10nm-30nm;

[0011] And / or, the thickness of the second electrode layer is 5nm-20nm.

[0012] In some embodiments of the present application, the first permanent magnetic material includes a rare earth permanent magnetic alloy;

[0013] And / or, the magnetic energy product of the permanent magnetic material is between 15mGOe and 50mGOe;

[0014] And / or, the permanent magnetic material is selected from at least one of samarium cobalt permanent magnets and neodymium iron boron permanent magnets.

[0015] In some embodiments of the present application, the first magnetic functional layer includes the first permanent magnetic material and the first electrode material, and the mass ratio of the first electrode material to the first permanent magnetic material in the first magnetic functional layer is (3:2) to 1;

[0016] And / or, the first electrode is selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0017] A second aspect of the present application provides a method for preparing a composite electrode, the preparation method comprising:

[0018] Providing a first electrode layer, the first electrode layer comprising a first electrode material; stacking a first magnetic functional layer on the first electrode layer, the first magnetic functional layer comprising the first electrode material and a first permanent magnetic material; magnetizing the stacked first electrode layer and the first magnetic functional layer in a magnetic field environment; stacking a second electrode layer on the magnetized first magnetic functional layer; wherein the material forming the second electrode layer is the same as the material forming the first electrode layer;

[0019] Alternatively, a first electrode layer is provided, the first electrode layer includes a first electrode material; a first magnetic functional layer is stacked on the first electrode layer, the first magnetic functional layer includes the first electrode material and a first permanent magnetic material; a second electrode is prepared on the first magnetic functional layer, the material forming the second electrode layer is the same as the material forming the first electrode layer; and the stacked first electrode layer, the first magnetic functional layer and the second electrode layer are magnetized in a magnetic field environment.

[0020] In some embodiments of the present application, the first permanent magnetic material includes a rare earth permanent magnetic alloy;

[0021] And / or, the magnetic energy product of the first permanent magnetic material is between 15mGOe and 50mGOe.

[0022] In some embodiments of the present application, the optoelectronic device includes a cathode, an anode, and a functional layer disposed between the cathode and the anode;

[0023] The cathode and / or the anode include the composite electrode, or the cathode and / or the anode are prepared by the composite electrode preparation method.

[0024] In some embodiments of the present application, the optoelectronic device further includes a reflective layer, wherein the reflective layer is disposed on a side of the anode facing away from the functional layer, and the reflective layer includes a second permanent magnetic material.

[0025] In some embodiments of the present application, the second permanent magnetic material is selected from at least one of samarium cobalt permanent magnets and neodymium iron boron permanent magnets.

[0026] In some embodiments of the present application, the reflective layer includes a first reflective layer, a second magnetic functional layer, and a second reflective layer stacked in sequence, and the second magnetic functional layer includes the second permanent magnetic material.

[0027] In some embodiments of the present application, the optoelectronic device further includes an encapsulation layer, and the encapsulation layer is arranged on a side of the cathode away from the functional layer.

[0028] In some embodiments of the present application, the packaging layer further includes a resin matrix and an electromagnetic shielding material, and the volume ratio of the electromagnetic shielding material to the resin matrix is ​​between 5% and 10%.

[0029] In some embodiments of the present application, the functional layer includes a light-emitting layer, and the material of the light-emitting layer is independently selected from one or more quantum dot light-emitting materials, and the quantum dot light-emitting material is selected from one or more of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials. The material of the single-structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots are selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, and the II-VI group compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, At least one of HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, At least one of PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, In At least one of NAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2, and the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH 2) nNH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or,

[0030] The functional layer comprises an electron transport layer, the material of the electron transport layer is selected from at least one of metal oxides, doped metal oxides, 2-6 group semiconductor materials, 3-5 group semiconductor materials and 1-3-6 group semiconductor materials, the metal oxide is selected from at least one of ZnO, BaO, TiO2 and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2 and SnO2, the doping element is selected from at least one of Al, Mg, Li, In and Ga, the 2-6 group semiconductor material is selected from at least one of ZnS, ZnSe and CdS; the 3-5 group semiconductor material is selected from at least one of InP and GaP; the 1-3-6 group semiconductor material is selected from at least one of CuInS and CuGaS; and / or,

[0031] The functional layer includes a hole transport layer, and the materials of the hole transport layer are independently selected from 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-di(4-(N,N'-diphenyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, -diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), Poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl benzidine, PEDOT:PSS and its derivatives, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives At least one of biological materials, poly (9,9-octylfluorene) and its derivatives, poly (spirofluorene) and its derivatives, N, N'-di (naphthalene-1-yl) -N, N'-diphenylbenzidine, spiro NPB, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or,

[0032] The functional layer includes a hole injection layer, and the material of the hole injection layer is independently selected from at least one of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0033] A third aspect of the present application provides a display device, comprising the optoelectronic device.

[0034] The present application provides a composite electrode, a preparation method and a photoelectric device. The composite electrode in the present application includes a permanent magnetic material, so that the magnetized composite electrode can maintain a relatively stable resistance value in a magnetic field environment, thereby improving the performance stability of the photoelectric device having the composite electrode in a magnetic field environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 A structural block diagram of an optoelectronic device according to an embodiment of the present application;

[0037] Figure 2 A schematic diagram of the structure of an anode in an embodiment of the present application;

[0038] Figure 3 A schematic diagram of the structure of a cathode in an embodiment of the present application;

[0039] Figure 4 A schematic structural diagram of a first embodiment of an optoelectronic device of the present application;

[0040] Figure 5 A schematic structural diagram of a second embodiment of an optoelectronic device of the present application;

[0041] Figure 6 A schematic structural diagram of a third embodiment of an optoelectronic device of the present application.

[0042] Figure numerals: 100, optoelectronic device; 110, anode; 120, cathode; 130, first electrode layer; 140, magnetic functional layer; 150, second electrode layer; 160, functional layer; 161, electron transport layer; 162, light-emitting layer; 163, hole transport layer; 164, hole injection layer; 170, ITO substrate. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0044] In this application, the word "exemplary" is used to mean "serving as an example, illustration, or illustration." Any embodiment described in this application as "exemplary" is not necessarily to be construed as being preferred or advantageous over other embodiments. The following description is given to enable any person skilled in the art to implement and use the invention. In the following description, details are listed for the purpose of explanation. It should be understood that a person of ordinary skill in the art can recognize that the invention can be implemented without using these specific details. In other instances, well-known structures and processes are not elaborated in detail to avoid obscuring the description of the invention with unnecessary details. Therefore, the present invention is not intended to be limited to the embodiments shown, but is consistent with the widest scope consistent with the principles and features disclosed in this application.

[0045] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0046] The embodiment of the present application provides a photoelectric device. The photoelectric device in the present application has higher current efficiency and brightness, and longer service life.

[0047] See also Figures 1 to 3 , Figure 1 1 is a schematic diagram of a structure of a photoelectric device in an embodiment of the present application. The photoelectric device 100 includes a cathode 120, an anode 110, and a functional layer 160 disposed between the cathode and the anode. The cathode 120 and the anode 110 are used to connect to a power source so that the power source supplies power to the photoelectric device 100. At least one of the cathode 120 and the anode 110 is a composite electrode. In some embodiments of the present application, please refer to Figure 3 The cathode 120 includes a composite electrode, and the cathode 120 includes a first electrode 130 layer, a magnetic functional layer 140 and a second electrode 150 layer. The anode 110 is an electrode known in the prior art. For example, the anode 110 is an ITO substrate 170 and a silver reflective layer. Figure 2, the anode 110 includes a composite electrode, and the anode 110 includes an ITO substrate 170, a first electrode layer 130, a magnetic functional layer 140 and a second electrode 150 layer which are stacked. The cathode 120 is an electrode known in the prior art, and illustratively, the cathode is a silver electrode. Further, the first electrode layer 130 is a silver layer, and the thickness of the first electrode layer 130 is greater than 100nm. Exemplarily, the thickness of the first electrode layer 130 is between 100nm and 200nm, so as to ensure that the first electrode layer 130 is not light-transmissive and can act as a silver reflective layer, thereby simplifying the structure of the composite electrode. In some other embodiments of the present application, the cathode 120 and the anode 110 both include a composite electrode. The composite electrode in the present application can maintain a relatively stable resistance value in a magnetic field environment after magnetization, thereby improving the performance stability of the optoelectronic device 100 having the composite electrode in a magnetic field environment. The composite electrode is described in detail below in conjunction with specific embodiments.

[0048] The composite electrode in the present application includes a first electrode layer 130, a magnetic functional layer 140 and a second electrode layer 150 which are stacked in sequence. The first electrode layer 130 includes a first electrode material. The magnetic functional layer 140 includes the first electrode material and a permanent magnetic material. The material forming the second electrode layer 150 is the same as the material forming the first electrode layer. In the present application, the first electrode layer 130 is arranged on one side of the magnetic functional layer 140, and the second electrode layer 150 is arranged on the other side of the magnetic functional layer 140, and the materials used to prepare the first electrode layer 130 and the second electrode layer 150 are the same, so that electrons can be stably injected into the light-emitting layer when the composite electrode is working. In addition, the magnetic functional layer 140 also includes a permanent magnetic material, so that the magnetized composite electrode can maintain a relatively stable resistance value in a magnetic field environment, thereby improving the performance stability of the optoelectronic device having the composite electrode in a magnetic field environment.

[0049] It should be noted that permanent magnetic material refers to a material that can maintain constant magnetism once magnetized. It is understandable that in a magnetic field environment, the existing electrodes cannot maintain a stable resistance value due to the magnetoresistance effect, which has a great impact on the stability of device performance. Based on this, the present application proposes a composite electrode, the magnetic functional layer of the composite electrode includes a permanent magnetic material, and after the composite electrode is magnetized in a magnetic field, the extremely high hysteresis of the permanent magnet will make the resistance of the composite electrode no longer change significantly, thereby improving the performance stability of the optoelectronic device having the composite electrode in a magnetic field environment.

[0050] In the present application, the first electrode material includes, but is not limited to, one or more of a metal material, a carbon material, and a metal oxide. Among them, the metal material includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, and Mg. The carbon material includes one or more of graphite, carbon nanotubes, graphene, and carbon fiber. The metal oxide may be a doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, and AMO. It can be understood that the first electrode material is a conventional material for preparing an electrode, that is, the material used to prepare the first electrode does not belong to the main improvement point of the present application, and will not be further elaborated here.

[0051] In some embodiments of the present application, the permanent magnetic material includes a rare earth permanent magnetic alloy. Rare earth permanent magnetic alloy refers to a rare earth metal as an alloying element. Rare earth permanent magnetic alloys have excellent permanent magnetic properties. For example, the maximum magnetic energy product of rare earth permanent magnetic alloys is 5 to 10 times that of traditional permanent magnetic materials such as aluminum nickel cobalt and ferrite, or even higher. In this embodiment, the use of rare earth permanent magnetic alloys to prepare the magnetic functional layer is conducive to further improving the resistance stability of the composite electrode, thereby improving the performance stability of the optoelectronic device having the composite electrode in a magnetic field environment.

[0052] In some embodiments of the present application, the permanent magnetic material includes a rare earth permanent magnetic alloy, and the functional layer includes a quantum dot light-emitting layer. The rare earth permanent magnetic alloy has strong stability and weak diffusion ability of metal ions, thereby reducing the probability of metal ions diffusing into other functional layers of quantum dots, which is beneficial to improving the stability of quantum dot devices. In other embodiments of the present application, the functional layer includes an organic light-emitting layer. In other embodiments of the present application, the permanent magnetic material can also be an aluminum-nickel-cobalt permanent magnetic alloy, an iron-chromium-cobalt permanent magnetic alloy, a permanent magnetic ferrite, and a composite permanent magnetic material.

[0053] Further, the permanent magnetic material is selected from at least one of samarium cobalt permanent magnets (SmCo) and neodymium iron boron (NdFeB) permanent magnets. It is understood that the magnetic energy product of samarium cobalt magnets is between 15mGOe and 30mGOe. The magnetic energy product of neodymium iron boron magnets is between 27mGOe and 50mGOe. After the composite electrode in this embodiment is magnetized in a magnetic field, the extremely high hysteresis of the permanent magnet will make the resistance of the composite electrode change less in a magnetic field environment.

[0054] In some embodiments of the present application, the magnetic energy product of the permanent magnetic material is between 15mGOe and 60mGOe. It is understandable that the magnetic energy product is one of the important parameters for measuring the amount of energy stored in a magnet. The larger the magnetic energy product of the permanent magnetic material, the higher the hysteresis of the permanent magnet obtained after magnetization, which is conducive to improving the resistance stability of the composite electrode.

[0055] In some embodiments of the present application, the thickness of the magnetic functional layer 140 is between 10nm and 30nm. Exemplarily, the thickness of the magnetic functional layer is 10nm, or 14nm, or 18nm, or 22nm, or 25nm, or 27, or 30nm. Further, the thickness of the magnetic functional layer is between 15nm and 25nm. It is understandable that if the thickness of the magnetic functional layer is too thin, for example, the thickness of the magnetic functional layer is less than 10nm, it is easy to cause the hysteresis of the composite electrode to be not significantly improved after magnetization, which is not conducive to the stability of the composite electrode in a magnetic field environment. If the thickness of the magnetic functional layer is too thick, for example, the thickness of the magnetic functional layer is greater than 30nm, the cost of the composite electrode will increase and the volume will increase.

[0056] In some embodiments of the present application, the thickness of the first electrode layer 130 is between 3nm and 10nm. Exemplarily, the thickness of the first electrode layer is 3nm, or 5nm, or 6nm, or 8nm, or 10nm. Further, the thickness of the first electrode layer is between 4nm and 7nm. It is understood that if the thickness of the first electrode layer is too thin, for example, the thickness of the first electrode layer is less than 3nm, it is easy to cause unstable electron injection when the composite electrode is working. If the thickness of the first electrode layer is too thick, for example, the thickness of the first electrode layer is greater than 10nm, the cost of the composite electrode is increased and the volume is increased.

[0057] In some embodiments of the present application, the first electrode layer 130 is between 90nm and 150nm. Exemplarily, the thickness of the first electrode layer is 90nm, or 100nm, or 115nm, or 120nm, or 130nm, or 135, or 140nm, or 145, or 150nm. Further, the thickness of the first electrode layer is 100nm-120nm. It is understandable that if the thickness of the first electrode layer is too thin, for example, the thickness of the first electrode layer is less than 90nm, it is easy to cause the composite electrode to be transparent. If the thickness of the first electrode layer is too thick, for example, the thickness of the first electrode layer is greater than 150nm, the cost of the composite electrode is increased and the volume is increased.

[0058] In some embodiments of the present application, the thickness of the second electrode layer 150 is between 3nm and 20nm. Exemplarily, the thickness of the second electrode layer is 3nm, or 5nm, or 6nm, or 8nm, 10nm, or 12nm, or 16nm, or 18nm, or 20nm. Further, the thickness of the second electrode layer is between 4nm and 10nm. It is understandable that if the thickness of the second electrode layer is too thin, for example, the thickness of the second electrode layer is less than 3nm, it is easy to cause unstable electron injection when the composite electrode is working. If the thickness of the second electrode layer is too thick, for example, the thickness of the second electrode layer is greater than 20nm, the cost of the composite electrode is increased and the volume is increased.

[0059] In some embodiments of the present application, the thickness of the first electrode layer 130 is between 4nm and 7nm, the thickness of the magnetic functional layer 140 is between 15nm and 25nm, and the thickness of the second electrode layer 150 is between 8nm and 12nm. The composite electrode of this embodiment has good stability in a magnetic field environment after magnetization, has a small thickness change, and can stably inject electrons when the composite electrode is working.

[0060] In some embodiments of the present application, the mass ratio of the first electrode material to the permanent magnetic material in the magnetic functional layer 140 is between 3:2 and 1:1. It is understandable that if the mass ratio of the permanent magnetic material in the magnetic functional layer is too low, for example, less than 50%, it is easy to cause the resistance stability of the magnetized composite electrode in the magnetic field to be unsatisfactory. If the mass ratio of the permanent magnetic material in the magnetic functional layer is too high, for example, less than 67%, it is easy to cause the electron injection ability of the composite electrode to be significantly deteriorated.

[0061] In some embodiments of the present application, the functional layer 160 includes an electron transport layer 161, a light emitting layer 162, a hole transport layer 163, and a hole injection layer 164. The materials of the functional layer 160, the electron transport layer 161, the light emitting layer 162, the hole transport layer 163, and the hole injection layer 164 have been specifically described above and will not be repeated here.

[0062] In some embodiments of the present application, the optoelectronic device further includes a reflective layer; the reflective layer includes a first reflective layer, a second magnetic functional layer and a second reflective layer stacked in sequence. The second magnetic functional layer includes a permanent magnetic material. Specifically, the first reflective layer and the second reflective layer are both metal reflective layers, such as a silver layer. The second magnetic functional layer is selected from at least one of a samarium cobalt permanent magnet (SmCo) and a neodymium iron boron (NdFeB) permanent magnet.

[0063] In some embodiments of the present application, the optoelectronic device further includes a packaging layer, the packaging layer includes a resin matrix and an electromagnetic shielding material, and the volume ratio of the electromagnetic shielding material to the resin matrix is ​​between 5% and 10%.

[0064] Another aspect of the present application provides a method for preparing a composite electrode, the method comprising:

[0065] Step S1 provides a first electrode layer, wherein the first electrode layer includes a first electrode material. Exemplarily, the first electrode layer is prepared by a vapor deposition process using the first electrode material. The first electrode material has been specifically described above and will not be further described here. A person skilled in the art may select a suitable vapor deposition process according to the specific material, which will not be further described here.

[0066] Step S2 is to prepare a magnetic functional layer by stacking on the first electrode layer, wherein the magnetic functional layer includes the first electrode material and a permanent magnetic material. Exemplarily, the first electrode material and the permanent magnetic material are simultaneously evaporated according to a preset raw material ratio (for example, the mass ratio of the first electrode material to the permanent magnetic material is 1:1) to form a magnetic functional layer. That is, the magnetic functional layer is prepared by a process of co-evaporating the first electrode material and the permanent magnetic material. Among them, the permanent magnetic material has been specifically described above and will not be further described here.

[0067] Step S3 magnetizes the stacked first electrode layer and magnetic functional layer in a magnetic field environment. Exemplarily, the stacked first electrode layer and magnetic functional layer are placed in a magnetic field environment (field strength 1000 μt) for 5-20 minutes to fully magnetize them.

[0068] Step S4: preparing a second electrode layer on the magnetized magnetic functional layer, wherein the material forming the second electrode layer is the same as the material forming the first electrode layer, to obtain a composite electrode.

[0069] The present application also provides another method for preparing a composite electrode, the preparation method comprising:

[0070] Step S1 provides a first electrode layer, wherein the first electrode layer includes a first electrode material. Exemplarily, the first electrode layer is prepared by a vapor deposition process using the first electrode material. The first electrode material has been specifically described above and will not be further described here. A person skilled in the art may select a suitable vapor deposition process according to the specific material, which will not be further described here.

[0071] Step S2 is to prepare a magnetic functional layer by stacking on the first electrode layer, wherein the magnetic functional layer includes the first electrode material and a permanent magnetic material. Exemplarily, the first electrode material and the permanent magnetic material are simultaneously evaporated according to a preset raw material ratio (for example, the mass ratio of the first electrode material to the permanent magnetic material is 1:1) to form a magnetic functional layer. That is, the magnetic functional layer is prepared by a process of co-evaporating the first electrode material and the permanent magnetic material. Among them, the permanent magnetic material has been specifically described above and will not be further described here.

[0072] Step S5: preparing a second electrode layer on the magnetic functional layer, wherein the material forming the second electrode layer is the same as the material forming the first electrode layer.

[0073] Step S6: magnetize the stacked first electrode layer, magnetic functional layer and second electrode layer in a magnetic field environment. For example, the stacked first electrode layer, magnetic functional layer and second electrode layer are placed in a magnetic field environment (field strength 1000 μt) for 5 min to 20 min to fully magnetize them and obtain a composite electrode.

[0074] Composite electrode embodiment 1 (composite electrode related embodiment)

[0075] Step 1: Evaporate an Ag layer on the substrate with a vacuum degree not higher than 3x10-4Pa, a speed of 1 angstrom / second, and a thickness of 3nm to obtain a first electrode layer.

[0076] Step 2: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag and NdFeB (the mass ratio of Ag to NdFeB is 1:1) are simultaneously evaporated on the first electrode layer at a rate of 1 angstrom / second and a thickness of 20 nm to obtain a semi-finished device with a magnetic functional layer.

[0077] Step 3: Place the semi-finished device in a magnetic field environment (field strength 1000 μt) for 10 minutes to fully magnetize it.

[0078] Step 4: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag was evaporated on the magnetic functional layer at a rate of 1 angstrom / second and a thickness of 20 nm to prepare a second electrode layer to obtain a composite electrode.

[0079] Composite electrode example 2

[0080] Step 1: Evaporate an Ag layer on the substrate with a vacuum degree not higher than 3x10-4Pa, a speed of 1 angstrom / second, and a thickness of 10nm to obtain a first electrode layer.

[0081] Step 2: Ag and SmCo (the mass ratio of Ag and SmCo is 3:2) are simultaneously deposited on the first electrode layer by thermal evaporation with a vacuum degree not higher than 3x10-4Pa at a rate of 1 angstrom / second and a thickness of 30nm to obtain a semi-finished device with a magnetic functional layer.

[0082] Step 3: Place the semi-finished device in a magnetic field environment (field strength 1000 μt) for 10 minutes to fully magnetize it.

[0083] Step 4: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag was evaporated on the magnetic functional layer at a rate of 1 angstrom / second and a thickness of 5 nm to prepare a second electrode layer to obtain a composite electrode.

[0084] Composite electrode example 3

[0085] Step 1: Evaporate an Ag layer on the substrate with a vacuum degree not higher than 3x10-4Pa, a speed of 1 angstrom / second, and a thickness of 4nm to obtain a first electrode layer.

[0086] Step 2: Vacuum not higher than 3x10 by thermal evaporation -4Pa, Ag and AlNiCo (the mass ratio of Ag to AlNiCo is 2:1) are simultaneously evaporated on the first electrode layer at a rate of 1 angstrom / second and a thickness of 10 nm to obtain a semi-finished device with a magnetic functional layer.

[0087] Step 3: Place the semi-finished device in a magnetic field environment (field strength 1000 μt) for 10 minutes to fully magnetize it.

[0088] Step 4: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag was evaporated on the magnetic functional layer at a rate of 1 angstrom / second, for 100 seconds, with a thickness of 15 nm, to prepare a second electrode layer to obtain a composite electrode.

[0089] Composite electrode embodiment 4

[0090] Step 1: Evaporate an Ag layer on the substrate with a vacuum degree not higher than 3x10-4Pa, a speed of 1 angstrom / second, and a thickness of 4nm to obtain a first electrode layer.

[0091] Step 2: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag and AlNiCo (the mass ratio of Ag to AlNiCo is 2:1) are simultaneously evaporated on the first electrode layer at a rate of 1 angstrom / second and a thickness of 10 nm to obtain a semi-finished device with a magnetic functional layer.

[0092] Step 3: Ag is evaporated on the magnetic functional layer at a rate of 1 angstrom / second, for 100 seconds, with a thickness of 15 nm to obtain a second electrode layer.

[0093] Step 4: Place the stacked first electrode, magnetic functional layer and second electrode in a magnetic field environment (field strength 1000 μt) for 10 minutes to fully magnetize them and obtain a composite electrode.

[0094] Composite electrode comparative example 1

[0095] Step 1: Evaporate an Ag layer on the substrate with a vacuum degree not higher than 3x10-4Pa, a speed of 1 angstrom / second, and a thickness of 23nm to obtain an electrode.

[0096] Device Example 1

[0097] Step 1: Prepare a hole injection layer by spin coating on an ITO substrate. The material is PEDOT:PSS, the rotation speed is 5000 r / min, the time is 30 seconds, and then heated at 150° C. for 15 minutes to form a hole injection layer.

[0098] Step 2: Spin-coat TFB (8 mg / mL) on the PEDOT:PSS layer at a speed of 3000 r / min for 30 seconds, and then heat at 120°C for 10 minutes to form a hole transport layer.

[0099] Step 3: Prepare a quantum dot light-emitting layer by spin coating on the hole transport layer. The quantum dot material is CdZnSe (20 mg / mL), the rotation speed is 2000 r / min, and the time is 30 seconds.

[0100] Step 4: Prepare an electron transport layer by spin coating on the quantum dot light-emitting layer. The material is ZnO (30 mg / mL), the rotation speed is 3000 r / min, and the time is 30 seconds.

[0101] Step 5: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag was evaporated on the electron transport layer at a rate of 1 angstrom / second, for 50 seconds, with a thickness of 5 nm, to obtain a first electrode layer.

[0102] Step 6: Vacuum no higher than 3x10 by thermal evaporation -4 Pa, Ag and NdFeB (the mass ratio of Ag to NdFeB is 1:1) are simultaneously evaporated on the first electrode layer at a rate of 1 angstrom / second, a time of 200 seconds, and a thickness of 20 nm to obtain a semi-finished device with a magnetic functional layer.

[0103] Step 7: Place the semi-finished device in a magnetic field environment (field strength 1000 μt) for 10 minutes to fully magnetize it.

[0104] Step 8: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag was evaporated on the magnetic functional layer at a rate of 1 angstrom / second, for 100 seconds, with a thickness of 10 nm, to obtain a second electrode layer.

[0105] Step 9: The device is encapsulated with epoxy resin, and the thickness of the encapsulation layer is about 5 microns. The experimental sample 1 is obtained. The specific structure is as follows Figure 4 shown.

[0106] Device Example 2

[0107] The difference between the embodiment 1 and the embodiment 1 is that: the bottom of the device substrate has a reflective layer, that is, before step 1, it also includes:

[0108] Step S1: Optimize the device substrate. During the preparation of the bottom reflective layer of the substrate, thermal evaporation is first performed with a vacuum degree not higher than 3x10 -4 Pa, evaporate Ag at a rate of 1 angstrom / second, for 500 seconds, with a thickness of 50nm.

[0109] Step S2 is carried out by thermal evaporation, and the vacuum degree is not higher than 3x10 -4 Pa, evaporate NdFeB at a rate of 1 angstrom / second, for 300 seconds, with a thickness of 30nm, and let it stand for 10min under a field strength of 1000μt to fully magnetize it.

[0110] Step S3 optimizes the device substrate. During the preparation of the bottom reflective layer of the substrate, thermal evaporation is first performed with a vacuum degree of no more than 3x10 -4 Pa, evaporate Ag at a rate of 1 angstrom / second, for 1200 seconds, with a thickness of 120nm.

[0111] The preparation of the hole injection layer, hole transport layer, quantum dot light-emitting layer, electron transport layer, first electrode, magnetic functional layer, magnetization step, second electrode, and device packaging after step S3 are the same as those in Example 1. Experimental sample 2 is obtained. The specific structure is as follows Figure 5 shown.

[0112] Device Example 3

[0113] The difference between this embodiment and Example 2 is that the device packaging process is different. Specifically, the device is coated with epoxy resin to form a packaging layer, and the thickness of the packaging layer is about 3 microns. A shielding material (the volume ratio of epoxy resin to carbon black (Conductex40-220) is 8%) is coated on the packaging layer to form a shielding layer, and the thickness of the shielding layer is about 2 microns. Experimental sample 3 is obtained. The specific structure is as follows Figure 6 shown.

[0114] Device Example 4

[0115] The difference from Example 1 is that the mass ratio of Ag to NdFeB in step 6 is 3:2. Experimental sample 4 is obtained.

[0116] Device Example 5

[0117] The difference from Example 1 is that the mass ratio of Ag to NdFeB in step 6 is 4:3. Experimental sample 5 is obtained.

[0118] Device Example 6

[0119] The difference from Example 1 is that the mass ratio of Ag to NdFeB in step 6 is 3:1. Experimental sample 6 is obtained.

[0120] Device Example 7

[0121] The difference between the embodiment 1 and the embodiment 1 is that the permanent magnetic material in step 6 is SmCo, and the mass ratio of Ag to SmCo is 1:1. Experimental sample 7 is obtained.

[0122] Device Example 8

[0123] The difference between the embodiment 1 and the embodiment 1 is that the permanent magnetic material in step 6 is aluminum nickel cobalt, and the mass ratio of Ag to aluminum nickel cobalt is 1:1. Experimental sample 8 is obtained.

[0124] Device Example 9

[0125] The difference between this embodiment and the first embodiment is that the device is an inverted device. The specific steps are as follows.

[0126] Step 1: Prepare an electron transport layer by spin coating on an ITO substrate. The material is ZnO (30 mg / mL), the rotation speed is 3000 r / min, and the time is 30 seconds.

[0127] Step 2: Spin coating the electron transport layer to prepare a quantum dot light-emitting layer. The quantum dot material is CdZnSe (20 mg / mL), the rotation speed is 2000 r / min, and the time is 30 seconds.

[0128] Step 3: Spin-coat TFB (8 mg / mL) on the quantum dot light-emitting layer at a rotation speed of 3000 r / min for 30 seconds, and then heat at 120° C. for 10 minutes to form a hole transport layer.

[0129] Step 4: Prepare a hole injection layer by spin coating on the hole transport layer. The material is PEDOT:PSS, the rotation speed is 5000r / min, the time is 30 seconds, and then heated at 150°C for 15 minutes to form a hole injection layer.

[0130] Step 5: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag was evaporated on the hole injection layer at a rate of 1 angstrom / second, for 50 seconds, with a thickness of 5 nm, to obtain a first electrode layer.

[0131] Step 6: Vacuum no higher than 3x10 by thermal evaporation -4 Pa, Ag and NdFeB (the mass ratio of Ag to NdFeB is 1:1) are simultaneously evaporated on the first electrode layer at a rate of 1 angstrom / second, a time of 200 seconds, and a thickness of 20 nm to obtain a semi-finished device with a magnetic functional layer.

[0132] Step 7: Place the semi-finished device in a magnetic field environment (field strength 1000 μt) for 10 minutes to fully magnetize it.

[0133] Step 8: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag was evaporated on the magnetic functional layer at a rate of 1 angstrom / second, for 100 seconds, with a thickness of 10 nm, to obtain a second electrode layer.

[0134] Step 9: The device is encapsulated with epoxy resin, and the thickness of the encapsulation layer is about 5 microns. Experimental sample 9 is obtained.

[0135] Device Example 10

[0136] The difference between the embodiment 9 and the embodiment 9 is that: the bottom of the device substrate has a reflective layer, that is, before step 1, it also includes:

[0137] S1 optimizes the device substrate by thermal evaporation, with a vacuum degree no higher than 3x10 -4 Pa, Ag was evaporated on one side of the substrate at a rate of 1 angstrom / second, for 500 seconds, with a thickness of 50nm.

[0138] S2 is evaporated by heat, the vacuum degree is not higher than 3x10 -4 Pa, evaporate NdFeB at a rate of 1 angstrom / second, for 300 seconds, with a thickness of 30nm, and let it stand for 10min under a field strength of 1000μt to fully magnetize it.

[0139] S3 optimizes the device substrate. During the preparation of the bottom reflective layer of the substrate, thermal evaporation is first performed with a vacuum degree not higher than 3x10 -4 Pa, evaporate Ag at a rate of 1 angstrom / second, for 1200 seconds, with a thickness of 120nm.

[0140] Device Example 11

[0141] The difference between this embodiment and Example 10 is that the device packaging process is different. Specifically, the device is coated with epoxy resin to form a packaging layer, and the thickness of the packaging layer is about 3 microns. A shielding material (the volume ratio of epoxy resin to carbon black (Conductex40-220) is 8%) is coated on the packaging layer to form a shielding layer, and the thickness of the shielding layer is about 2 microns.

[0142] Device Example 12

[0143] The difference between the embodiment 1 and the embodiment 1 is that step 7 and step 8, that is, the order of step 7 and step 8 is swapped.

[0144] Step 7: Vacuum no higher than 3x10 by thermal evaporation -4 Pa, Ag was evaporated on the magnetic functional layer at a rate of 1 angstrom / second, for 100 seconds, with a thickness of 10 nm, to obtain a second electrode layer.

[0145] Step 8: Place the stacked first electrode, magnetic functional layer and second electrode in a magnetic field environment (field strength 1000 μt) for 10 minutes to fully magnetize them.

[0146] Device Example 13

[0147] Step 1: Prepare a hole injection layer by spin coating on an ITO substrate. The material is PEDOT:PSS, the rotation speed is 5000 r / min, the time is 30 seconds, and then heated at 150° C. for 15 minutes to form a hole injection layer.

[0148] Step 2: Spin-coat TFB (8 mg / mL) on the PEDOT:PSS layer at a speed of 3000 r / min for 30 seconds, and then heat at 120°C for 10 minutes to form a hole transport layer.

[0149] Step 3: Prepare a quantum dot light-emitting layer by spin coating on the first hole transport layer. The quantum dot material is CdZnSe (20 mg / mL), the rotation speed is 2000 r / min, and the time is 30 seconds.

[0150] Step 4: Prepare an electron transport layer by spin coating on the quantum dot light-emitting layer. The material is ZnO (30 mg / mL), the rotation speed is 3000 r / min, and the time is 30 seconds.

[0151] Step 5: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, Ag and NdFeB (the mass ratio of Ag to NdFeB is 1:1) are simultaneously evaporated on the electron transport layer at a rate of 1 angstrom / second, a time of 200 seconds, and a thickness of 20 nm to obtain a semi-finished device with a magnetic functional layer.

[0152] Step 6: Place the semi-finished device in a magnetic field environment (field strength 1000 μt) for 10 minutes to fully magnetize it.

[0153] Step 7: The device is encapsulated with epoxy resin, and the thickness of the encapsulation layer is about 5 microns.

[0154] Device Example 14

[0155] The difference between this embodiment and embodiment 1 is that step 8 is deleted.

[0156] Device Example 15

[0157] The difference between this embodiment and Example 1 is that in step 1, the vacuum degree is not higher than 3x10 -4 Pa, Ag was evaporated to form a reflective layer with a thickness of 200nm.

[0158] Device Example 16

[0159] The difference between this embodiment and Example 15 is that in step 1, the side of the ITO substrate facing away from the hole transport layer is evaporated by heat, and the vacuum degree is not higher than 3x10 -4 Pa, and Ag and NdFeB (the mass ratio of Ag to NdFeB is 1:1) are simultaneously evaporated to form a reflective layer with a thickness of 200nm.

[0160] Device Comparative Example 1

[0161] Step 1: Prepare the first hole injection layer by spin coating on the ITO substrate. The material is PEDOT:PSS, the rotation speed is 5000, the time is 30 seconds, and then heat at 150° C. for 15 minutes to form the first hole injection layer.

[0162] Step 2: Spin-coat TFB (8 mg / mL) on the PEDOT:PSS layer at a speed of 3000 r / min for 30 seconds, followed by heating at 120°C for 10 minutes.

[0163] Step 3: Prepare a quantum dot light-emitting layer by spin coating on the first hole transport layer. The quantum dot material is CdZnSe (20 mg / mL), the rotation speed is 2000 r / min, and the time is 30 seconds.

[0164] Step 4: Prepare the first electron transport layer by spin coating on the quantum dot light-emitting layer. The material is ZnO (30 mg / mL), the rotation speed is 3000 r / min, and the time is 30 seconds.

[0165] Step 5: Vacuum not higher than 3x10 by thermal evaporation -4 Pa, evaporate Ag (silver), the speed is 1 angstrom / second, the time is 200 seconds, the thickness is 20nm.

[0166] Step 6: The device is encapsulated with epoxy resin, and the thickness of the encapsulation layer is about 5 microns. Comparative sample 1 is obtained.

[0167] Device Comparison Example 2

[0168] Step 1: Optimize the device substrate. During the preparation of the bottom reflective layer of the substrate, thermal evaporation is first performed with a vacuum degree not higher than 3x10 -4 Pa, evaporated Ag, thickness 200nm.

[0169] Step 2: Spin coating the side of the ITO substrate away from the reflective layer to prepare the first hole injection layer. The material is PEDOT:PSS, the rotation speed is 5000, the time is 30 seconds, and then heated at 150° C. for 15 minutes to form the first hole injection layer.

[0170] Step 3: Spin-coat TFB (8 mg / mL) on the PEDOT:PSS layer at a speed of 3000 r / min for 30 seconds, followed by heating at 120°C for 10 minutes.

[0171] Step 4: Spin coating the first hole transport layer to prepare a quantum dot light-emitting layer, the quantum dot material is CdZnSe (20 mg / mL), the rotation speed is 2000 r / min, and the time is 30 seconds.

[0172] Step 5: Prepare the first electron transport layer by spin coating on the quantum dot light-emitting layer. The material is ZnO (30 mg / mL), the rotation speed is 3000 r / min, and the time is 30 seconds.

[0173] Step 6: Vacuum no higher than 3x10 by thermal evaporation -4 Pa, evaporate Ag (silver), the speed is 1 angstrom / second, the time is 200 seconds, the thickness is 20nm.

[0174] Step 7: The device is encapsulated with epoxy resin, and the thickness of the encapsulation layer is about 5 microns. Comparative sample 1 is obtained.

[0175] The photoelectric efficiency and working life of the different sample devices obtained in Examples 1-16 and Comparative Examples 1 and 2 were tested at different magnetic field intensities and with a constant current of 2 mA. The results are shown in Table 1. T95-1K represents the time taken for the brightness of the device to decay from 100% to 95% at a brightness of 1000 nit. This value is calculated from the values ​​of L and T95. CE represents the current efficiency of the device. Under the premise that the area of ​​the luminous area and the driving current are consistent, the higher the CE, the better the device performance.

[0176] Table 1

[0177]

[0178]

[0179] It can be seen from the experimental data in Table 1 that the performance of the devices in Comparative Samples 1 and 2 drops sharply in a magnetic field environment, resulting in a significant reduction in their service life, and the higher the magnetic field strength, the more significant the performance drop. Permanent magnetic materials are set in the electrodes of the devices of Experimental Samples 1 to 16. Although the performance of the devices in a magnetic field environment will be reduced, there is a significant improvement over the devices in Comparative Samples 1 and 2. The T95-1K of most devices in a magnetic field environment (magnetic field strength 50μt) is reduced by less than 20% relative to an environment without a magnetic field. It can be seen from Example 3 that a composite electrode containing a permanent magnetic material is set in the device, and a shielding layer is set on the packaging layer so that the performance of the device in a magnetic field environment is almost unchanged, that is, it has excellent stability in a magnetic field environment. .

[0180] In addition, experimental samples 9 to 11 are inverted devices, and their overall carrier injection is different from that of other experimental samples (upright devices), resulting in lower T95-1K values ​​in an environment without a magnetic field. However, the decrease in their T95-1K values ​​in a magnetic field environment is smaller than that in an environment without a magnetic field, and the devices still have good performance stability in a magnetic field environment.

[0181] The above is a detailed introduction to a composite electrode, a preparation method and a photoelectric device provided in the embodiments of the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A composite electrode, characterized in that: include: A first electrode material and a first permanent magnetic material.

2. The composite electrode according to claim 1, characterized in that The composite electrode comprises a first electrode layer, a first magnetic functional layer and a second electrode layer which are stacked in sequence; The first electrode layer includes the first electrode material, and the first magnetic functional layer includes the first permanent magnetic material.

3. The composite electrode according to claim 2, characterized in that The material forming the second electrode layer is the same as the material forming the first electrode layer; And / or, the first magnetic functional layer further includes the first electrode material; And / or, the thickness of the first electrode layer is 3nm-10nm; And / or, the thickness of the first magnetic functional layer is 10nm-30nm; And / or, the thickness of the second electrode layer is 5nm-20nm.

4. The composite electrode according to claim 1, characterized in that The first permanent magnetic material includes a rare earth permanent magnetic alloy; And / or, the magnetic energy product of the first permanent magnetic material is between 15mGOe and 50mGOe; And / or, the first permanent magnetic material is selected from at least one of samarium cobalt permanent magnets and neodymium iron boron permanent magnets.

5. The composite electrode according to claim 2, characterized in that The first magnetic functional layer includes the first permanent magnetic material and the first electrode material, and the mass ratio of the first electrode material to the first permanent magnetic material in the first magnetic functional layer is (3:2) to 1; And / or, the first electrode is selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode, the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, and the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

6. A method for preparing a composite electrode, characterized in that: The preparation method comprises: Providing a first electrode layer, the first electrode layer comprising a first electrode material; stacking a first magnetic functional layer on the first electrode layer, the first magnetic functional layer comprising the first electrode material and a first permanent magnetic material; magnetizing the stacked first electrode layer and the first magnetic functional layer in a magnetic field environment; stacking a second electrode layer on the magnetized first magnetic functional layer; wherein the material forming the second electrode layer is the same as the material forming the first electrode layer; Alternatively, a first electrode layer is provided, the first electrode layer includes a first electrode material; a first magnetic functional layer is stacked on the first electrode layer, the first magnetic functional layer includes the first electrode material and a first permanent magnetic material; a second electrode is prepared on the first magnetic functional layer, the material forming the second electrode layer is the same as the material forming the first electrode layer; and the stacked first electrode layer, the first magnetic functional layer and the second electrode layer are magnetized in a magnetic field environment.

7. The preparation method according to claim 6, characterized in that: The first permanent magnetic material includes a rare earth permanent magnetic alloy; And / or, the magnetic energy product of the first permanent magnetic material is between 15mGOe and 50mGOe.

8. A photoelectric device, characterized in that: The photoelectric device comprises a cathode, an anode and a functional layer disposed between the cathode and the anode; The cathode and / or the anode comprises the composite electrode according to any one of claims 1 to 5, or the cathode and / or the anode is prepared by the composite electrode preparation method according to claims 6 to 7.

9. The optoelectronic device according to claim 8, characterized in that The optoelectronic device further includes a reflective layer, which is arranged on a side of the anode away from the functional layer, and the reflective layer includes a second permanent magnetic material.

10. The optoelectronic device according to claim 9, characterized in that The second permanent magnetic material is selected from at least one of samarium cobalt permanent magnets and neodymium iron boron permanent magnets.

11. The optoelectronic device according to claim 9, characterized in that The reflective layer includes a first reflective layer, a second magnetic functional layer and a second reflective layer which are stacked in sequence, and the second magnetic functional layer includes the second permanent magnetic material.

12. The optoelectronic device according to claim 8, characterized in that The optoelectronic device further comprises a packaging layer, wherein the packaging layer is arranged on a side of the cathode away from the functional layer.

13. The optoelectronic device according to claim 12, characterized in that The packaging layer also includes a resin matrix and an electromagnetic shielding material, and the volume ratio of the electromagnetic shielding material to the resin matrix is ​​between 5% and 10%.

14. The optoelectronic device according to claim 8, characterized in that The functional layer comprises a light-emitting layer, wherein the material of the light-emitting layer is independently selected from one or more quantum dot light-emitting materials, wherein the quantum dot light-emitting material is selected from one or more single-structure quantum dots, core-shell quantum dots and perovskite semiconductor materials, wherein the material of the single-structure quantum dots, the core material of the core-shell quantum dots and the shell material of the core-shell quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, wherein the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe , CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, Pb At least one of SnSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs At least one of InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2, and the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH 2) nNH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or, The functional layer comprises an electron transport layer, the material of the electron transport layer is selected from at least one of metal oxides, doped metal oxides, 2-6 group semiconductor materials, 3-5 group semiconductor materials and 1-3-6 group semiconductor materials, the metal oxide is selected from at least one of ZnO, BaO, TiO2 and SnO2; the metal oxide in the doped metal oxide is selected from at least one of ZnO, TiO2 and SnO2, the doping element is selected from at least one of Al, Mg, Li, In and Ga, the 2-6 group semiconductor material is selected from at least one of ZnS, ZnSe and CdS; the 3-5 group semiconductor material is selected from at least one of InP and GaP; the 1-3-6 group semiconductor material is selected from at least one of CuInS and CuGaS; and / or, The functional layer includes a hole transport layer, and the materials of the hole transport layer are independently selected from 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-di(4-(N,N'-diphenyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, -diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylenevinylene), Poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraaryl benzidine, PEDOT:PSS and its derivatives, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives At least one of biological materials, poly (9,9-octylfluorene) and its derivatives, poly (spirofluorene) and its derivatives, N, N'-di (naphthalene-1-yl) -N, N'-diphenylbenzidine, spiro NPB, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or, The functional layer includes a hole injection layer, and the material of the hole injection layer is independently selected from at least one of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

15. A display device, characterized in that: The optoelectronic device comprises the optoelectronic device according to any one of claims 8 to 14.